?VISCOSITY OF LITHIUM CHLORIDE SOLUTIONS IN WATER-METHANOL MIXTURES - UDDIN, FAHIM; NAIM, M. AEJAZ; SAEED, REHANA; HUSSAIN, IQBAL (Biological Sciences - PJSIR, 1995)
The viscositiesofLiCI in aqueousmethanolsolution(10 -50%)weremeasuredatvariousconcentrations (1.0X 102 to 8.0X 10.2 mol.drn’) andtemperatures (30-46°C) respectively.The viscositywas interpreted in terms ofJones-Dole and Root density equations. Jone-Dole coefficients A and B and Root equation constants were evaluated by linear extrapolation using the least square method.The positive and increasing value of Jone-Dole B-coefticients lead to the conclusionthatlithiumchlorideinaqueousmethanolbehavesasstructureenhancer.Differentactivationparameterssuch as energy of activation ( E),free energy change ( GN) and entropy change of activation ( S") at different solvent composition and salt concentrations were also evaluated.